The Influence of Lean Six-Sigma Tools in Reducing the Cost of Quality and Fulfilling of Competitive Advantage of Firms - Ebraheem Alobaidy, Rasha Jasim Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
Today, firms are seeking to improve their value at the market in line with increasing their revenues. Firms employ several strategies to achieve this goal. Lean Six Sigma (LSS) is a new trend in quality management practices. The aim of this article is to investigate the contribution of LLS in reducing the cost of quality and fulfilling the competitive advantage of firms. To achieve this aim, the researcher used the qualitative and quantitative methods, employing the questionnaire survey tool. The study sample consisted of 98 participants. Data was analyzed using Statistical Package for the Social Sciences (SPSS). Books, papers of journals, and several papers of conferences were revised. The analysis of literature shows that LLS is considered a significant strategy for improving the efficiency of firms' processes and customer satisfaction. It also indicates that LLS assists organizations in improving the quality of their services or products in parallel with reducing their expenses, which is reflected in fostering firms' competitive advantage.